ANALISIS TINGKAT RESIKO SISTEMIK DAN KETERKAITAN FINANSIAL PERBANKAN DI INDONESIA - Aprisal W. Malale; Dony Abdul Chalid (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2014)
This article aims to Analyze the level of sistemic risk in the banking sector of indonesia to see trade linkages and value of the shares of the banks in indonesia . The study was conducted on 16 banks whose shares are actively traded on the indonesia stock exchange, by using quantile regression with CoVar research model. The measurement result and systemic risk analysis showed that the the majority of individual banks provide additional contributions to the overall concluded that the individual risk of a banks that is conditioned to the risk of other bank generates additional diverse risks. It is confirmed that when a bank experiencing distries, this condition does not necessarily provide additional individual risk to other banks. Based on these results, it is suggested to the government to carry out special supervision by OJK to banks with high systemic risk contrubution and strong and strong financial linkages with other banks by monitoring the movement of its shares.